Development of energy renovation packages for the Danish residential sector. (February 2019) - Pomianowski, Michal; Antonov, Yovko Ivanov; Heiselberg, Per
Abstract: The work presented in this paper is developed as a part of the Horizon 2020 EU project REFURB. The number of deep energy retrofits is falling behind the EU ambitious targets. The REFURB project aims at finding technical and nontechnical solutions that match the demand and supply side of the residential building renovation market. Due to the multiple significant differences at the national level, compelling offers are developed specifically for each country participant. This paper elaborates only on the Danish approach. The Danish approach to create compelling offers for pre-selected homeowner target groups is based on (I) selection of dwelling segment with high impact and energy saving potential, (II) sequenced approach in creating renovation package solutions, (III) compelling offer to be proposed with specific timing. This paper focuses mainly on the second listed component, namely, development of the renovation package solutions. The paper only briefly highlights the selection of dwelling segment and does not present the creation of compelling offer due to the length of the paper. Initially, developed renovation packages are optimized purely focusing on the least-cost optimal, theoretical, energy savings. As a result, very rational packages were developed that were not met with acceptance from the building sector stakeholders. After several surveys and meetings with renovation market stakeholders such as building owners, energy renovation contractors, financial institutions, and energy consultants, the initial renovation packages were redefined in order to take account for factors such as securing investment in the renovated real estate, comfort, architectural aesthetic, and "low hanging fruit" energy saving solutions. Finally, ten different customized renovation packages were developed ranging between up to 7.500 and 62.000 € and bringing theoretical primary energy savings between 30 and up to 80%.